Neuroendocrine Cell Carcinoma of Unknown Primary Arising in Long Standing History of Multiple Sclerosis - Stergios Boussios; Vasiliki Kostadima; Anna Batistatou; Ioannis Tourkantonis; George Fotopoulos; Maria I. Argyropoulou; Nicholas Pavlidis (Case Reports in Oncological Medicine)
Multiple sclerosis (MS) is a chronic autoimmune disease that targets myelinated axons in the central nervous system (CNS). Cancer of unknown primary site (CUP) is a well-recognised clinical disorder, accounting for 3–5% of all malignant epithelial tumors. CUP is clinically characterised as an aggressive disease with early dissemination. Studies of cancer risk in MS patients have shown inconsistent findings. An increased risk of malignancy in patients with MS has been suggested, but recently serious questions have been raised regarding this association. Use of disease-modifying therapies might contribute to an increased cancer risk in selected MS patients. The concurrence of MS and CUP is exceptionally rare. Here we describe the case of a neuroendocrine carcinoma of unknown primary diagnosed in a male patient with a nine-year history of MS. The discussion includes data from all available population-based register studies with estimates of certain malignancies in patients with MS.